Pavement policies: unraveling the Norwegian ban on skateboarding - Langseth, Tommy; Bergsgard, Nils Asle (Frontiers in Sports and Active Living, 2025)
This paper investigates the historical prohibition of skateboarding in Norway from 1977 to 1989, a unique instance of such a comprehensive ban globally. The study aims to understand the circumstances leading to this ban and the rationale behind it. Two primary explanations emerged around the ban: one from a bureaucratic perspective citing risk management, and the other from skateboarders seeing it as a regulation of their counterculture. We argue that neither narrative alone is sufficient, proposing instead that other mechanisms were at play. Firstly, the ban was the inaugural case under the newly enacted Product Control Act, which was initially designed to address environmental issues. The State Pollution Control Authority found itself ill-prepared to handle the new responsibilities inherent in product control, resulting in diffuse responsibilities across several agencies. Secondly, the ambiguous categorization of skateboards as toys rather than sports equipment influenced the decision to enact the ban. The timing of the skateboard phenomenon coincided with the passing of the Product Control Act, suggesting a case of a solution seeking a problem. In conclusion, we posit that the skateboard ban resulted from a complex interplay of factors, including novel legislation, ambiguous responsibilities, cultural categorizations, and coincidental timing, rather than being solely a response to risk management or counterculture curtailment.